A novel diffraction tomographic algorithm with narrow observation angle. (28th February 2019) - Yang, Chunxia; Zhang, Jian; Tong, Meisong
Abstract: Conventional diffraction tomography (DT) can be used to reconstruct objects with 360° coverage of observation angle. But solving inverse problem could be challenging when the full angle data are not available. In this paper, a novel diffraction tomographic algorithm with extrapolation method is proposed to detect two‐dimensional (2D) dielectric objects in cases where the observation stations are far away from the search domain and the observation angles are limited to a narrow range. Extrapolation is introduced to obtain more data in the frequency domain. Using this algorithm, all locations, shapes, and dielectric properties of targets can be reconstructed under 90° or even narrower observation angle. Due to the use of fast Fourier transform in the implementation, this algorithm is very fast although many iterations of extrapolation are needed. Images can be reconstructed with nearly real‐time performance. Simulation results are given to show the validity of the algorithm.